Efficacy and Safety of PD-1/PD-L1 Inhibitors Plus Chemotherapy Versus PD-1/PD-L1 Inhibitors in Advanced Non-Small Cell Lung Cancer: A Network Analysis of Randomized Controlled Trials - Li, Xiang; Yan, Shi; Yang, Jichun; Wang, Yaqi; Lv, Chao; Li, Shaolei; Zhao, Jun; Yang, Yue; Zhuo, Minglei; Wu, Nan (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICIs) are recommended as first-line treatment for late-stage non-small cell lung cancer (NSCLC), either as monotherapy or in combination with chemotherapy. However, efficacy and safety comparisons between ICIs as monotherapy and ICIs with chemotherapy are lacking. We searched PubMed, Embase, and Cochrane Library for randomized controlled trials published before February 29th, 2020, with the search terms ‘immunotherapy’ and ‘chemotherapy’. Ten eligible trials were identified with a total of 5956 patients. Of these patients, 3204 received immune therapy and 2752 received chemotherapy. PD-1 inhibitors with chemotherapy improved OS (HR 0.84, 0.77-0.92), PFS (HR 0.80, 0.75-0.85), and objective response rate (ORR) (odds ratio (OR) 2.55, 1.20-5.28) compared to PD-1 inhibitors as monotherapy. In contrast, PD-L1 inhibitors plus chemotherapy showed no significant differences in OS, PFS, or ORR compared with PD-L1 inhibitors as monotherapy. When patients were stratified according to PD-L1 expression level, patients with high PD-L1 expression (≥ 50%) receiving PD-1 inhibitors plus chemotherapy had improved PFS, but not other outcomes, compared to PD-1 inhibitors as monotherapy. In these patients, PD-L1 inhibitors plus chemotherapy showed no significant difference in survival compared with PD-L1 inhibitors. In the low PD-L1 expression group (1-49%), PD-1 inhibitors plus chemotherapy improved OS and PFS, but no advantage was observed in PD-L1 inhibitors plus chemotherapy in OS, PFS, or ORR compared with PD-L1 inhibitor monotherapy. When comparing PD-1/PD-L1 inhibitors plus chemotherapy with PD-1/PD-L1 inhibitors monotherapy, no significant differences were observed in the rate of immune-related adverse events (AEs). In summary, for treating patients with late-stage NSCLC, PD-1 inhibitors plus chemotherapy have improved efficacy compared with PD-1 inhibitor monotherapy, but PD-L1 inhibitors plus chemotherapy have similar efficacy as PD-L1 monotherapy. Survival benefits of PD-1/PD-L1 inhibitors combined with chemotherapy were particularly significant in patients with low PD-L1 expression levels.